Approximate state-space and transfer function models for 2x2 linear hyperbolic systems with collocated boundary inputs - Bartecki, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
Two approximate representations are proposed for distributed parameter systems described by two linear hyperbolic PDEs with two time- and space-dependent state variables and two collocated boundary inputs. Using the method of lines with the backward difference scheme, the original PDEs are transformed into a set of ODEs and expressed in the form of a finite number of dynamical subsystems (sections).
Keywords: distributed parameter system; hyperbolic equations; approximation model; state space; transfer function